2021
DOI: 10.1039/d1nr02620h
|View full text |Cite|
|
Sign up to set email alerts
|

Long cyclic stability of acidic aqueous zinc-ion batteries achieved by atomic layer deposition: the effect of the induced orientation growth of the Zn anode

Abstract: Aqueous Zn-ion batteries with economical ZnSO4 solution as electrolyte are suffered from the tremendous tendency of dendrite formation under the condition of alkalinity while utilization of Zn(CF3SO3)2 delivers superior performance...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…The rate capacities of Zn or TM–OH@Zn symmetric cells (shown in Figure d,e) further intuitively confirm the improvement of the rate capacity and long-term stability after modification by the TM–OH-based layer. Known from Table , compared with some reported research work, ,,,,,,, TM–OH@Zn symmetric cells in this study also show notable long-term stability and low polarization voltage.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The rate capacities of Zn or TM–OH@Zn symmetric cells (shown in Figure d,e) further intuitively confirm the improvement of the rate capacity and long-term stability after modification by the TM–OH-based layer. Known from Table , compared with some reported research work, ,,,,,,, TM–OH@Zn symmetric cells in this study also show notable long-term stability and low polarization voltage.…”
Section: Resultssupporting
confidence: 66%
“…Contemporary methods to control Zn dendrite growth and improve the corrosion-resistant performance of Zn anodes have been investigated to optimize the electrochemical performance of Zn anode. Coating conductive materials (e.g., graphene or Mxenes) with special structures or their composite materials on Zn anodes can control Zn dendrite growth by changing the nucleation conditions and providing a more uniformly distributed electric field. , Some well-designed inorganic nanomaterials layer (e.g., TiO 2 , ZrO 2 , and Al 2 O 3 ) have been confirmed to prevent corrosion from electrolytes and positively guide the uniform growth of Zn dendrites. Moreover, some materials based on organic compounds or multicomponent composites have also been applied for the surface modification of Zn anodes. ,, Apart from the surface modification of Zn anodes, various Zn anodes with specific compositions have been developed to improve the cyclic stability of ZIBs. Even though these meaningful strategies have been applied to promote the comprehensive electrochemical behavior of Zn anodes, developing ideal Zn anodes equipped with specific intrinsic features of excellent Zn 2+ conductivity, dendrite-free, good electrolyte wettability, and outstanding corrosion resistance is a popular research topic.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most accurate surface-coating methods, atomic layer deposition (ALD) has been widely applied to solve the interfacial issues of the electrodes in various battery systems. For the cathode protection in ZIBs, the ultrathin ALD layer with controllable thickness would not only protect the electrode from the undesirable side reaction at the interface to inhibit the cathode dissolution but also act as the artificial cathode electrolyte interphase to allow the transference of zinc ions. Guo et al first reported an atomic layer-deposited HfO 2 protective layer on the Zn 3 V 2 O 7 (OH) 2 ·2H 2 O cathode as an artificial solid electrolyte interphase .…”
Section: Introductionmentioning
confidence: 99%
“…Considering the effect of the surface atomic structure, the zinc corrosion and H 2 evolution could be effectively weakened. As a consequence, the induced exposure of the zinc (002) plane would be beneficial for the reversibility and stability of the zinc anode. Graphene, with a hexagonal lattice structure, is reported to be effective in driving deposition of the (002) plane because of the small lattice mismatch (7.4%). The resultant epitaxial Zn anode presents superior reversibility (CE exceeding 99.7%) over thousands of cycles .…”
Section: Introductionmentioning
confidence: 99%